Prediction of Uniaxial Compressive Strength of Granite Rock Samples of Lugoba Quarry Using Rebound Hammer Test - Kongola, Moses; Baruti, Karim R. (Tanzania Journal of Engineering and Technology, 2021)
Rebound hammer test is widely used as an indirect measure of uniaxial compressive strength for engineering materials such as concrete, soil, and rock in both civil and mining engineering works. In quarries, uniaxial compressive strength is a crucial parameter in the analysis of geotechnical problems involving rock stability and rock blasting design. This study aims at establishing the empirical models of uniaxial compressive strength fits on rebound hammer number that can be used to predict uniaxial compressive strength of granitic rock at Lugoba Quarry. Data for direct uniaxial compressive strength were obtained from uniaxial compressive strength test carried out on 20 core samples at the Dar es Salaam Institute of Technology Geotechnical Laboratory using ISMR Standard Procedures. The rebound hammer test was carried out using testing hammer type N. The tests were done horizontally on two scanline's geotechnical domains of the rock mass on the footwall side of the quarry. The obtained results of UCS ranging from 105 to 132.5 MPa and RHN from 44.90 to 49.5 were found to be comparable with values of other granitic rocks in other parts of the world. Regression Analysis using SPSS software was carried out to develop 5 regression models of UCS vs.RHN. The values of obtained in this study were found to be between 0.93 and 0.95, which are comparable with other studies. This implies that RHN accounted between 93 and 95% of the total variation of the UCS and the relationships were very strong. Two models; Logarithmic and exponential were found to be appropriate and recommended for application at Lugoba Quarry. Keywords: Uniaxial compressive strength, Rebound hammer number, Granitic rock, Regression model.